Fetal foot length for assessment of gestational age: a cross sectional study - Sharma, Vaibhav; Saxena, Ruchi; Gaur, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Fetal age actually begins at conception and an equivalent term is conceptional age. Uncertain gestational age (GA) has been associated with adverse pregnancy outcomes independent of maternal characteristics. The objective was to evaluate the accuracy of fetal foot length (FFL) in estimation of gestational age. Methods: It was a cross sectional study. Trans abdominal ultrasound on 150 pregnant women with normal singleton pregnancies between 16 to 40 weeks was done to measure FFL. The relationship between GA and FFL was analysed by simple linear regression. Results: A linear relationship was demonstrated between FFL and GA. (GA (in weeks)=7.490+0.393×FFL (in mm)) with significant correlation (r=0.985, p<0.001). Conclusions: Ultrasonographic measurement of FFL is a reliable indicator of gestational age and can be a useful alternative to estimate GA when other routine biometric parameters are not conclusive.